2016
DOI: 10.1017/s0890060416000056
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of example familiarity and modality on design fixation

Abstract: Design fixation is a factor that negatively influences the generation of novel design concepts (Jansson & Smith, 1991;Moreno et al., 2015;Smith et al., 1993). When designers fixate, they tend to reproduce example features or features from their initial ideas. In order to mitigate design fixation, it is crucial to identify the factors that influence the extent of design fixation. This paper investigates two such factors -the modality of examples and the familiarity of designers with the example features. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
0
14
2
Order By: Relevance
“…Beginning engineers may have less prior knowledge of existing designs, along with little exposure to methods for generating diverse ideas. The observed findings may differ from studies with more advanced student engineers [17,39] and with expert engineers with more experience [26,28]. Further research is needed to address how prior domain knowledge influences fixation.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Beginning engineers may have less prior knowledge of existing designs, along with little exposure to methods for generating diverse ideas. The observed findings may differ from studies with more advanced student engineers [17,39] and with expert engineers with more experience [26,28]. Further research is needed to address how prior domain knowledge influences fixation.…”
Section: Discussioncontrasting
confidence: 58%
“…They reviewed 25 studies exploring factors such as modality of the example, number of examples provided, diversity, and novelty of examples; however, findings have been inconsistent across studies. Familiar examples produced more fixation [38,39], though Perttula and Silipä [40] found it also led to better design outcomes. Logically, the number of examples provided with a problem should impact fixation, but Perttula and Sipilä [40] and Dahl and Moreau [41] found no effect.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, those who were asked to use SCAMPER were given a four-page instructional aid, demonstrating how it could be applied towards concepts that reuse plastic bottles. Viswanathan et al (2016) showed that examples with familiar features caused more fixation. Therefore, examples in plasticbottle reuse were chosen as they were dissimilar to wind-turbine blades in both function and scale.…”
Section: A Methodsmentioning
confidence: 99%
“…Presumably, differences in feature repetition results between stimulated and non-stimulated participants are more pronounced when those features represent rare, unusual solutions to the design problem, thus being very unlikely to emerge during idea generation in non-SGs. Conversely, repetition results might be similar if the features analyzed represent obvious solutions, thus being highly likely to appear in ideas with or without external stimulation [although there is recent evidence to the contrary (Viswanathan et al, 2016)]. Though the features used in both our studies are easily comparable (i.e., following a similar structure and referring to the same bike parts), we believe that the features used in study 2 were more common than those in study 1, especially the “ extendable components to change bike size ”, which frequently appeared in the designs of all groups.…”
Section: Studymentioning
confidence: 99%
“…Design researchers have studied many different aspects of the inspiration process, including characteristics of external stimuli or inspiration sources (e.g., the modality of representation used for the stimuli) (Linsey et al, 2008; Sarkar & Chakrabarti, 2008; Atilola & Linsey, 2015; Viswanathan et al, 2016) and aspects of the design process (e.g., time available for ideation) (Youmans, 2011 a ; Tsenn et al, 2014; Siangliulue et al, 2015). One of the stimuli characteristics that has been studied is whether the quality of the examples (i.e., good or bad) would influence feature repetition, or whether those examples would be copied indiscriminately.…”
Section: Inspiration Fixation and The Introduction Of External Stimulimentioning
confidence: 99%